Science, technology and innovation for sustainable cities and peri-urban communities (UN New YorkUS, 2013)
Provides an overview of how science, technology and innovation can address key challenges of rapid urbanisation, particularly in developing countries. Proposes technology and policy options for consideration by national governments and the international community, with a view to promoting sustainable urban development
Keywords: URBAN DEVELOPMENT